Drug Safety Crises Management in Pharmacovigilance - Gloria Shalviri; Kheirollah Gholami; Reza Majdzadeh (Research Center for Rational Use of Drugs (RCRUD), 2018)
Background: Adverse drug events can cause serious consequences including death. A published report by Lazarou et al in 1998 showed that adverse drug events were the 4th to 6th leading cause of death in the United States. These events may lead to drug safety crises in some issues, which need to take crises management process for solving the problem and/or preventing similar events. Objectives: To evaluate nature of drug safety crises based on adverse events reported to Iranian Pharmacovigilance Center from 1999 through 2012. To mention success and failure outcomes of crises management process taken against detected crises. Methods: All adverse drug events received by Iranian Pharmacovigilance Center from 1999 through 2012 were evaluated for reports with fatal outcome. All alerting letters and manuscripts published by the Center during the same period were reviewed for detailed information on detected crises. World Health Organization definition was used for detecting drug safety crises. Results: Among 42036 registered cases in our database, 463 deaths were recorded. The most frequent suspected drug for adverse events with fatal outcome was ceftriaxone (100 cases). Ten different drug safety crises issues were detected during the study period and their successful or failure outcomes were evaluated. There were 112 issued alerting letters and 17 published manuscript during the same period which was monitored for detailed information.   Conclusion: It is necessary for national pharmacovigilance centers to have prepared programs for crises management. This could be useful for reducing drug related mortality.